Selective photoinactivation of Histoplasma capsulatum by water-soluble derivatives chalcones - Melo, Wanessa C. M. A. [UNESP]; Santos, Mariana Bastos dos [UNESP]; Marques, Beatriz de Carvalho [UNESP]; Regasini, Luis Octavio [UNESP]; Soares Mendes Giannini, Maria Jose [UNESP]; Fusco Almeida, Ana Marisa [UNESP] (Elsevier B.V., 2017)
Histoplasmosis is a respiratory and systemic disease caused by the dimorphic fungus Histoplasma capsulatum. The clinical features may vary from asymptomatic infections to disseminated severe form depending of patient immunity. The treatment of histoplasmosis can be performed with itraconazole, fluconazole, and in the disseminated forms is used amphotericin B. However, the critical side effects of amphotericin B, the cases of itraconazole therapy failure and the appearance of fluconozole-resistant strains makes necessary the search of new strategies to treat this disease. Antimicrobial photodynamic therapy (aPDT) seems to be a potential candidate once have been show efficacy to inhibit others dimorphic fungi. Although the photosensitizer (PS) chalcone aggregates in biological medium, it has antifungal activity and show a high quantum yield of ROS formation. So, the aim of this study was to obtain the experimental parameters to achieve an acceptable selective chalcone water-soluble derivatives photoinactivation of H. capsulatum comparing with fibroblastic and keratinocytes cells which are the constituents of some potential host tissues. Yeast and cells were incubated with the same chalchones concentrations and short incubation time followed by irradiation with equal dose of light. The best conditions to kill H. capsulatum selectively were very low photosensitizers concentration (1.95 mu g mL(-1)) incubated by 15 min and irradiated with LED 450 nm with 24 J cm(-2). Key words: chalcone, Histoplasma capsulatum, aPDT, selectivity. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Chalcone; Histoplasma capsulatum; aPDT; Selectivity